Clinical research Functional scoliosis caused by leg length discrepancy - Raczkowski, Jan W.; Daniszewska, Barbara; Zolynski, Krystian (Archives of Medical Science, 2010)
Introduction: Leg length discrepancy (LLD) causes pelvic obliquity in the frontal plane and lumbar scoliosis with convexity towards the shorter extremity. Leg length discrepancy is observed in 3-15% of the population. Unequalized lower limb length discrepancy leads to posture deformation, gait asymmetry, low back pain and discopathy. Material and methods: In the years 1998-2006, 369 children, aged 5 to 17 years (209 girls, 160 boys) with LLD-related functional scoliosis were treated. An external or internal shoe lift was applied. Results: Among 369 children the discrepancy of 0.5 cm was observed in 27, 1 cm in 329, 1.5 cm in 9 and 2 cm in 4 children. During the first follow-up examination, within 2 weeks, the adjustment of the spine to new static conditions was noted and correction of the curve in 316 examined children (83.7%). In 53 children (14.7%) the correction was observed later and was accompanied by slight low back pain. The time needed for real equalization of limbs was 3 to 24 months. The time needed for real equalization of the discrepancy was 11.3 months. Conclusions: Leg length discrepancy equalization results in elimination of scoliosis. Leg length discrepancy < 2 cm is a static disorder; that is why measurements should be performed in a standing position using blocks of adequate thickness and the position of the posterior superior iliac spine should be estimated.